MENINGKATKAN HASIL BELAJAR SISWA KELAS XI MIPA C SMAS DARUL HIJRAH PUTERI MARTAPURA DENGAN MEDIA ALAT PERAGA MODEL SEL - RIANA SATRIYANI NUGROHO PUTRI (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2023)
This research aims to find out how to improve the learning outcomes of class XI MIPA C SMAS Darul Hijrah Puteri Martapura on the structure and function of cells using cell model aids in the 2022/2023 school year. This research was conducted in two cycles, each cycle consisting of planning, implementing, observing and reflecting. In cycle 1 the teaching aid used was a plant cell model while in cycle 2 the cell membrane model was used. The subjects of this research were students of class XI MIPA C SMAS Darul Hijrah Puteri Martapura with a total of 23 people. Data on learning outcomes were obtained using a learning outcomes test of 10 multiple choice questions. Students are said to be complete if they have a minimum KKM score of 75 and the achievement of success increases student learning outcomes by 75% of the number of students who score 75. Student learning outcomes in cycle 1 obtain an average score of 73 with completeness of 16 students or 69.57% and Cycle 2 obtained an average score of 78 with 18 students or 78.26% completeness. This shows an increase in student learning outcomes compared to before the research was carried out and the achievement of successful student learning outcomes by 78.26% exceeded the target achieved, which was 75% of the number of students who obtained a score of 75. Based on the research data, it can be concluded that the use of the tool demonstrating plant cell models and cell membranes can improve student learning outcomes on cell structure and function material ABSTRAKPenilitian ini bertujuan untuk mengetahui bagaimana meningkatkan hasil belajar siswa kelas XI MIPA C SMAS Darul Hijrah Puteri Martapura pada materi struktur dan fungsi sel dengan menggunakan alat peraga model sel pada tahun pelajaran 2022/2023. Penilitian ini dilakukan dengan dua siklus, setiap siklus terdiri dari perencanaan, pelaksanan, pengamatan dan refleksi. Pada siklus 1 alat peraga yang digunakan adalah model sel tumbuhan sedangkan siklus 2 model membran sel. Subjek penilitian ini adalah siswa kelas XI MIPA C SMAS Darul Hijrah Puteri Martapura dengan jumlah 23 orang. Data hasil belajar diperoleh dengan menggunakan tes hasil belajar sebanyak 10 soal pilih ganda. Siswa dikatakan tuntas apabila memiliki nilai KKM minimal 75 dan ketercapaian keberhasilan meningkatnya hasil belajar siswa sebesar 75% dari jumlah siswa yang memperoleh nilai 75. Hasil belajar siswa pada siklus 1 memperoleh nilai rata-rata 73 dengan ketuntasan sebanyak 16 siswa atau 69,57% dan siklus 2 memperoleh nilai rata-rata 78 dengan ketuntasan sebanyak 18 siswa atau 78,26%. Hal ini menunjukkan terjadi peningkatan hasil belajar siswa dibandingkan sebelum dilakukan penelitian dan ketercapaian keberhasilan hasil belajar siswa sebanyak 78, 26% melebihi dari target yang dicapai yaitu sebesar 75% dari jumlah siswa yang memperoleh nilai 75. Berdasarkan data hasil penelitian, dapat disimpulkan bahwa penggunaan alat peraga model sel tumbuhan dan membran sel dapat meningkatkan hasil belajar siswa pada materi struktur dan fungsi sel